2009
DOI: 10.1177/1059712309104966
|View full text |Cite
|
Sign up to set email alerts
|

Re-embodiment of Honeybee Aggregation Behavior in an Artificial Micro-Robotic System

Abstract: In this article we describe the re-embodiment of biological aggregation behavior of honeybees in Jasmine micro-robots. The observed insect behavior, in the context of the insect's sensor-actor system, is formalized as behavioral and motion-sensing meta-models. These meta-models are transformed into a sensor-actor system of micro-robots by means of a sensors virtualization technique. This allows us to keep the efficiency and scalability of the bio-inspired approach. We also demonstrate the systematic character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
160
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 15 publications
3
160
1
3
Order By: Relevance
“…Recent works (Kengyel et al, 2011;Kernbach et al, 2009) have shown that artificial agents controlled by this algorithm react flexible regarding environmental changes. In the work at hand we investigate how honey bees age polyethism influences this system.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works (Kengyel et al, 2011;Kernbach et al, 2009) have shown that artificial agents controlled by this algorithm react flexible regarding environmental changes. In the work at hand we investigate how honey bees age polyethism influences this system.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the evaluated individual behaviors of honeybees, 6,18 those behaviors are fitted in the described criteria of swarm robotics. 3 Inefficiency of a single bee to detect the optimal zone, simple perception of homogeneous individual agents, and effects of the population size are clearly illustrated in honeybee aggregation.…”
Section: Honeybee Aggregation Behaviormentioning
confidence: 99%
“…2 Schools of fish, flocks of birds, colonies of termites and ants, 4 foraging, 5 and aggregation of honeybees 6 are examples of swarm behavior. Ant colony optimization and particle swarm optimization are the most successful applications of swarm in problem solving that have been used in variety of applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective, networked or swarm robotics are scientific domains, dealing with cooperation in robotics [24]. Current research in these domains is mostly concentrated on cooperation and competition among stand-alone robots to increase their common fitness [25]. However, robots can build a principally new kind of collective systems, when to allow them to aggregate into a multi-robot organismlike-forms.…”
Section: Introductionmentioning
confidence: 99%